APPLICABILITY OF THE SOUTH AFRICAN DIABETES PREVENTION PROGRAMME IN THE EASTERN CAPE PROVINCE OF SOUTH AFRICA: A STUDY PROTOCOL. (June 2022) - Hill, Jillian; Yako, Yandiswa; Rusike, Constance; Toni, Simthandile; Musarurwa, Hannibal; Kengne, Andre Pascal
Abstract : Objective: South Africa (SA) is currently home to almost 14% of the estimated 19 million people living with diabetes in Sub-Saharan Africa (SSA). Urgent efforts are needed both to diagnose and appropriately manage South Africans with diabetes, as well as to prevent the progression to diabetes among those at high risk. While, there is definitive evidence on the effectiveness of lifestyle interventions in preventing the progression of diabetes among high risk people in high income countries, little is known about appropriate intervention approaches to be used in SA (within all nine provinces) and other SSA countries. The South African Diabetes Prevention Programme (SA-DPP) was initiated to generate such evidence for SA and inform similar initiatives in other countries in the region. The goal of the SA-DPP is to prevent or delay the occurrence of diabetes among high risk South Africans, with benefits extending to other major cardiometabolic risk factors that share behavioural determinants with T2DM. The purpose of this project is to implement and evaluate the suitability and applicability of the SA-DPP developed and tailored in urban populations in the Western Cape Province, in peri-urban populations in the Eastern Cape Province of South Africa. Design and method: We propose to implement and evaluate a DPP that has been adapted for SA, which was based on interventions previously shown to be effective in Finland and Australia. The SA-DPP trial is in its intermediate phases in Cape Town. We will use an open-labelled cluster randomized control design, with optional implementation of the intervention in the control clusters at the end of the study. 24 clusters across peri-urban communities in OR Tambo, Eastern Cape will be randomly allocated to participate in a lifestyle intervention facilitated by teams of non-professional health workers. Results: NA. Conclusions: Programme success will be assessed by comparing at 12-months participants in clusters receiving the intervention and those in the clusters not yet receiving the intervention for changes in: 1) body weight; 2) blood glucose, lipids, blood pressure, insulin sensitivity, diabetes risk score, albuminuria; 3) and incident diabetes; 4) safety and participant satisfaction. 4) Economic impact.